2013
DOI: 10.1113/jphysiol.2013.259150
|View full text |Cite
|
Sign up to set email alerts
|

Measuring cerebrovascular reactivity: what stimulus to use?

Abstract: Cerebrovascular reactivity is the change in cerebral blood flow in response to a vasodilatory or vasoconstrictive stimulus. Measuring variations of cerebrovascular reactivity between different regions of the brain has the potential to not only advance understanding of how the cerebral vasculature controls the distribution of blood flow but also to detect cerebrovascular pathophysiology. While there are standardized and repeatable methods for estimating the changes in cerebral blood flow in response to a vasoac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
315
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(326 citation statements)
references
References 109 publications
3
315
1
7
Order By: Relevance
“…With respect to CVR z-maps, the consistency of the stimulus, PaCO 2 , which is independent of the ventilatory response, 17 is a crucial enabling element. For example, the PaCO 2 stimuli resulting from breath-holding and inspiring a fixed PCO 2 are patient dependent and thus highly variable, 15 and therefore unsuitable. With a consistent PCO 2 stimulus, CVR z-scores should enable the comparison of CVR scores between centers.…”
Section: Characteristics Of the Patient Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to CVR z-maps, the consistency of the stimulus, PaCO 2 , which is independent of the ventilatory response, 17 is a crucial enabling element. For example, the PaCO 2 stimuli resulting from breath-holding and inspiring a fixed PCO 2 are patient dependent and thus highly variable, 15 and therefore unsuitable. With a consistent PCO 2 stimulus, CVR z-scores should enable the comparison of CVR scores between centers.…”
Section: Characteristics Of the Patient Cohortmentioning
confidence: 99%
“…The implementation of prospective end-tidal gas control has been described in detail elsewhere. 15 In brief, subjects were fitted with a face mask, and connected to a sequential gas delivery breathing circuit. 16 The patterns of PETCO 2 and PETO 2 were programmed into the automated gas blender (RespirAct TM , Thornhill Research, Toronto, Canada) running the prospective gas targeting algorithm of Slessarev et al 17 A standardized step CO 2 stimulus was implemented, consisting of the following sequence: a baseline PETCO 2 of 40 mm Hg for 60 seconds, step to a hypercapnia of 50 mm Hg for 45 seconds, baseline for 90 seconds, hypercapnia for 120 seconds, and return to baseline for 60 seconds, all during isoxic normoxia targeted at 100 mm Hg.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…6 Improvements of BOLD CVR methodologies have been proposed [13,15] and may increase sensitivity and quantification of (regional) CVR measurements in subjects with high-grade cerebral glioma.…”
Section: Limitations and Future Considerationsmentioning
confidence: 99%
“…[5] Cerebrovascular reactivity (CVR) is a functional parameter that can be assessed with MRI by obtaining Blood Oxygen-Level Dependent (BOLD) volumes. CVR is determined as the BOLD signal response due to deoxyhemoglobin washout related to carbon dioxide (CO 2 ) changes as the vasoactive stimulus, [6]and can be measured on high spatial resolution covering the entire brain. Using this concept, Hsu et al [7] have demonstrated that BOLD MRI generates CVR patterns to better distinguish normal brain tissue from glioma tissue.…”
Section: Introductionmentioning
confidence: 99%
“…(2007). Specific details and novelties of this technique as compared to other vasoactive stimuli have been described more specifically in a previous publication (Fierstra et al., 2013). The preprogrammed sequence consisted of an initial 100 s baseline P et CO 2 at 40 mmHg, after which a P et CO 2 step was increased to 10 mmHg above baseline for 80 s and a return to baseline for 100 s, before free breathing was restored.…”
Section: Methodsmentioning
confidence: 99%